Potensi Porphyra Sp. Asal Desa Allang, Pulau Ambon sebagai Sumber Pangan Fungsional Berbasis Makronutrien Lokal untuk Mendukung Kesehatan Masyarakat - Abdul Mahid Ukratalo; Martha Kaihena (Lembaga Pengembangan Kinerja Dosen, 2026)
Porphyra sp. seaweed is a marine biological resource with significant potential as a functional food ingredient, particularly in the coastal regions of Indonesia. This study aims to analyze the macronutrient content of Porphyra sp. from Desa Allang, Ambon Island, and to evaluate its potential as a functional food source based on local nutritional resources. Protein, carbohydrate, fat, moisture, and ash contents were analyzed using the AOAC method. The results indicate that Porphyra sp. contains 13.77% protein, 15.78% carbohydrates, and 1.35% fat, reflecting a high nutritional value with low fat content, thus meeting the characteristics of functional foods that provide health benefits to the community. The moisture content obtained was 11.55%, which is relatively low and is suspected to be influenced by the drying method using an oven. Furthermore, the ash content of 21.66% indicates a relatively high mineral content, contributing additional nutritional value that supports biological functions and overall health. The macronutrient composition is influenced by environmental factors such as habitat, water depth, water quality, and the growth phase of the seaweed. With its comprehensive nutritional profile, Porphyra sp. holds promise as a raw material for functional food development that not only fulfills nutritional requirements but also supports the enhancement of public health.